Edge‐Rich Reduced Graphene Oxide Embedded in Silica‐Based Laminated Ceramic Composites for Efficient and Robust Electrocatalytic Hydrogen Evolution. Issue 10 (16th August 2021) - Huang, Yujia; Wang, Min; Li, Yi; Yin, Shujia; Zhu, Hongwei; Wan, Chunlei
Abstract: To mitigate the energy crisis and environmental pollution, efficient and earth‐abundant hydrogen evolution reaction (HER) electrocatalysts are essential for hydrogen production through electrochemical water splitting. Graphene‐based materials as metal‐free catalysts have attracted significant attention but suffer from insufficient activity and stability. Therefore, a novel and economical approach is developed to prepare highly active, robust, and self‐supported reduced graphene oxide (rGO)/SiO2 ceramic composites as electrocatalysts in HER. Through intercalation and pressure sintering, the rGO sheets are parallelly aligned and embedded into a dense and chemically inert SiO2 matrix, ensuring the electrical conductivity and stability of the prepared composites. After directional cutting, the edges of the oriented rGO sheets become fully exposed on the composite surface, acting as highly electrocatalytic active sites in HER, as confirmed by density functional theory calculations. The 4 vol% rGO/SiO2 composite displays superior electrocatalytic performance, featuring a low overpotential (134 mV) at a current density of 10 mA cm −2, a small Tafel slope (103 mV dec −1 ), and excellent catalytic durability in 0.5 m H2 SO4 . This study provides a new yet cost‐effective strategy to prepare metal‐free, robust, and edge‐rich rGO/ceramic composites as a highly electrocatalytic active catalyst for HER applications. Abstract : A novel and facile method, intercalation combined with pressure sintering, is developed for preparing metal‐free, robust, and self‐supported electrodes of edge‐rich vertical graphene/ceramic composites.